NOWELIZACJA KODEKSU POSTĘPOWANIA W SPRAWACH O WYKROCZENIA - Stachowiak, Stanisław (Wydział Prawa i Administracji UAM, 2000)
Recently voted new Constitution of the Republic of Poland abolishes in its article 237 the boards judging petty offences and charges ordinary courts with judging these cases. The courts must presently be prepared - taking into account an adequate anticipatory period of time - to take over all these matters (there are a great many of them) on several different planes: structural (town or city courts must be organised), organisational, concerning offices and equipment and, last not least, the staff. Must also be changed a series of particular provisions in order to eliminate all possibility of a collision between new and formerly binding laws on these matters. An adequate temptation was made with the law from August 28, 1998, on change of the law-Code of petty offences, the law-Code of procedure in petty offences matters, the law on structure of the boards judging petty offences, the law-Labour Code as well as some other laws. In his article the Author discusses shortly particular new regulations within this scope and gives an analysis of expediency and advisability as well as tendencies of the changes in question.
AMENDING OF THE CODE OF PROCEDURE IN PETTY OFFENCES CASES